Community Psychology and the Acceptance of Rohingya Refugees in Aceh: Local Identity, Humanitarian Needs, and Islamic Law - Alwi, Said; Mukhlis; Siregar, Zulfikar Ali Buto; Iqbal, Muhammad; Fithra, Herman (Hikmatuna : Journal for Integrative Islamic Studies, 2024)
This research delves into the psychology of the Aceh community in receiving Rohingya refugees, with a particular emphasis on the influence of local identity. It critically analyzes mass media to identify reporting patterns and perspectives on Rohingya refugees. Data were gathered through news analysis and in-depth interviews to gain insights into the community's perceptions, attitudes, and local identity. The findings reveal that the Acehnese community's perceptions, attitudes, and emotional responses towards Rohingya refugees are shaped by a strong local identity, historical conflict experiences, and concerns about resource competition and religious identity. Acehnese cultural and religious identity promotes internal solidarity but also fosters exclusivity towards 'foreign' groups. Previous ethnic conflicts exacerbate tensions and distrust towards refugees. The use of religious symbols by refugees further heightens social and psychological tensions. However, the humanitarian principles in Islamic law, which emphasize fair treatment and assistance to those in need, play a pivotal role. This study adopts a multidimensional approach, integrating psychology, sociology, and education to address identity conflicts, foster harmonious interactions between the Acehnese community and Rohingya refugees, and strengthen intergroup relations by considering aspects of identity and humanity.